Cuneiform Texts from Babylonian Tablets in the British Museum. Part XXIII. Copies by R. Campbell Thompson, descriptive index, etc. by L. W. King - Budge, Ernest A. Wallis (1967)
First published by the Trustees of the British Museum, London (1906). Photolithographic Reprint 1967.